PERANAN PENGGUNAAN APLIKASI SHIPEDUCATION TRAINING GUNA MENINGKATKAN HASIL UJIAN KEAHLIAN PELAUT TARUNA TEKNOLOGI REKAYASA PERMESINAN KAPAL FAKULTAS VOKASI PELAYARAN UNIVERSITAS HANG TUAH - Sugeng Marsudi (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
This research investigates the influence of the ShipEducation Training Application on the test results of maritime cadets' skills in the Marine Engineering Technology Program, Faculty of Maritime Vocational Studies, Hang Tuah University. The main objective of the research is to analyze the impact of using this application on the understanding, skills, and test results of maritime cadets' skills. This study involves 150 respondents who use the ShipEducation Training Application in the learning process. Data analysis methods include descriptive statistics, correlation analysis, and linear regression. The research results indicate that the use of this application has a positive impact on the understanding and skills of maritime cadets. The average test results of active maritime cadets using the application reach 85%, while those who are not active only achieve 72%. Regression analysis shows a significant relationship between the frequency of using the ShipEducation Training Application and the skill test results, with a correlation coefficient of 0.67. Learning motivation factors also significantly influence test results. The findings of this research imply the importance of implementing educational technology in maritime education. In this context, the recommended actions include optimizing the promotion and training related to the ShipEducation Training Application for maritime cadets. The integration of technology into the curriculum also needs to be strengthened to support more adaptive and effective learning. Moreover, educational institutions need to encourage student learning motivation so that they become more active in using the application during the learning process. In conclusion, the ShipEducation Training Application plays a crucial role in enhancing the test results of maritime cadets' skills. By implementing the proposed recommendations, it is expected that the utilization of educational technology can be more optimal in preparing maritime cadets to meet the demands of the shipping industry. Keywords: ShipEducation Training Application, skill test results, maritime education, educational technology.